Approximate finite-dimensional ODE temperature model for microwave heating - Zhong, Jiaqi; Lianga, Shan; Zeng, Cheng; Yuan, Yupeng; Xiong, Qingyu (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, a finite-dimensional ordinary differential equation (ODE) model is proposed for predicting the temperature profile with microwave heating to accomplish lower computing complexity. The traditional parabolic partial different equation (PDE) model with integrating Maxwell’s equation and heat transport equation is not suitable for designing the on-line controller. Based on the obstruction, using an auxiliary function derives an intermediate model, which is analyzed and discussed for model reduction by employing the parameter separation method and Galerkin’s method. The simulation experiments on one-dimensional waveguide and cavity demonstrate that the proposed approximate model is effective.